2013
DOI: 10.3389/fnbeh.2013.00126
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Associative Memory from Childhood to Adulthood: A Behavioral and Neuroimaging Study

Abstract: Episodic memory refers to the capacity to bind multimodal memories to constitute a unique personal event. Most developmental studies on episodic memory focused on one specific component, i.e., the core factual information. The present study examines the relevance of a novel episodic paradigm to assess its developmental trajectories in a more comprehensive way according to the type of association (item-feature, item-location, and item-sequence associations) with measures of both objective and subjective recolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
1
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 79 publications
9
40
1
2
Order By: Relevance
“…This pattern of results is consistent with that reported by Guillery‐Girard et al. (), albeit the comparison in that study was made using two different behavioral tasks.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This pattern of results is consistent with that reported by Guillery‐Girard et al. (), albeit the comparison in that study was made using two different behavioral tasks.…”
Section: Discussionsupporting
confidence: 92%
“…While initial research had suggested that binding reached adult‐like operation in early childhood (Lloyd et al., ; Sluzenski et al., ), manipulating the episodic representation was associated with robust and diverging age‐related improvements in memory, despite using methods that should have substantially reduced the use and efficacy of controlled processes (e.g., encoding strategies; Bjorklund et al., ; Ghetti & Angelini, ), the predominate explanation of developmental improvements in episodic memory. These results are consistent with prior neuroimaging research that suggests a developing functional role of the hippocampus to binding operations (e.g., DeMaster & Ghetti, ; Guillery‐Girard et al., ; Lee et al., ). Together these data support the hypothesis that binding operations substantively contribute to episodic memory development in middle and late childhood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in contrast to a previous study by Guillery‐Girard et al. (), which also confirms the age between 9 and 10 years as a critical step in episodic development but rather suggests that memory for where events occur improves up until adulthood. This slow development appears to be partly due to the protracted maturation of the brain structures involved in episodic memory formation (Ghetti & Bunge, ; Gogtay et al., ).…”
contrasting
confidence: 66%
“…This age range covers different developmental stages, such as pre-and post-puberty, which might increase variability in brain structure and functions (especially regarding development of PFC), including memory 88 . This large developmental window could have accounted for the higher variance in task performance and, as a consequence, reduced the likelihood of finding significant group differences.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%